A flight control method for unmanned aerial vehicles based on vibration suppression. Issue 3 (26th March 2021) - Wang, Xinhua; Zhang, Xiulin; Gong, Huajun; Jiang, Ju; Rai, Hari Mohan
Abstract: The development of unmanned aerial vehicle (UAVs) has gained importance in recent years for various applications like photography, inspection of infrastructure and various agricultural applications. Various researchers have carried out numerous attempts at optimisation control of UAVs and their flight range maximisation. However, a few attempts have addressed structural deformation effects on the reliability and safety of UAVs. In order to study the effect of structural deformation on the reliability and safety of UAVs under normal flight conditions, a certain type of UAV as a research object is discussed and the augmented tracking model based on the original object system by using the Lyapunov function is built up. The performance is observed in terms of rise time and overshoot and it is observed from the simulation outcomes that the system is stable at all design points in the range of 0–9000 m, providing a rise time of 10 s and zero overshoot. From this study, it is revealed that the designed controller can effectively suppress the vibration of the flexible mode while ensuring the stability and tracking performance of the UAV.